2007
DOI: 10.1038/sj.ejcn.1602603
|View full text |Cite
|
Sign up to set email alerts
|

Effect of weight loss on the postprandial response to high-fat and high-carbohydrate meals in obese women

Abstract: Objective: To assess the effect of weight loss on the plasma lipid and remnant-like lipoprotein cholesterol (RLPc) response to a high-fat or a high-carbohydrate meal in a population of obese women. Design: Nutritional intervention study. Subjects: Sixteen obese women (mean body mass index (BMI): 37.675 kg/m 2 ). Methods: Subjects were asked to follow an energy-restricted diet (800 kcal/day) for 7 weeks, followed by a 1-week maintenance diet. Before and after weight loss, each participant was given (in random o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 34 publications
3
15
0
1
Order By: Relevance
“…Volek et al (39) found that obese women who lost a modest amount of weight on either a low-CHO diet (22.96 6 1.45 kg) or a low-fat diet (21.06 6 2.07 kg) significantly improved the AUC for TG following a fat-rich meal (229 and 225%, respectively). Insulin sensitivity only improved after the low-CHO diet; however, fasting insulin levels in both diets were lower than the post-weight loss amount reported by James et al Dallongeville et al (36) conducted a similar intervention study to assess the lipid response to a high-fat or high-CHO meal before and after weight loss. Obese women followed an energy-restricted diet (800 kcal/d) for 7 wk and reduced their body weight by~10% (P < 0.0001) with a concomitant decrease in TG (P = 0.0102), TC (P < 0.0001), LDL-C (P = 0.0003), and HDL-C (P = 0.0009).…”
Section: Inflammation Decreases Benefits Of Diet Interventionsmentioning
confidence: 88%
See 1 more Smart Citation
“…Volek et al (39) found that obese women who lost a modest amount of weight on either a low-CHO diet (22.96 6 1.45 kg) or a low-fat diet (21.06 6 2.07 kg) significantly improved the AUC for TG following a fat-rich meal (229 and 225%, respectively). Insulin sensitivity only improved after the low-CHO diet; however, fasting insulin levels in both diets were lower than the post-weight loss amount reported by James et al Dallongeville et al (36) conducted a similar intervention study to assess the lipid response to a high-fat or high-CHO meal before and after weight loss. Obese women followed an energy-restricted diet (800 kcal/d) for 7 wk and reduced their body weight by~10% (P < 0.0001) with a concomitant decrease in TG (P = 0.0102), TC (P < 0.0001), LDL-C (P = 0.0003), and HDL-C (P = 0.0009).…”
Section: Inflammation Decreases Benefits Of Diet Interventionsmentioning
confidence: 88%
“…Losing weight would be expected to contribute to a normalization of lipid metabolism. Numerous studies have reported beneficial effects of weight reduction on the postprandial lipid response in overweight individuals (36)(37)(38)(39). However, obese and insulin-resistant participants may require more aggressive dietary interventions to alter the lipid response, specifically, a greater weight reduction.…”
Section: Inflammation Decreases Benefits Of Diet Interventionsmentioning
confidence: 96%
“…For example, the response of chylomicrons (CM) to a fat meal can vary by up to 60% depending on the amount and quality of fat, carbohydrate and protein content [4,[5][6][7]. Additionally, chronic consumption of low energyhigh carbohydrate diets, often used for weight loss, has a tendency to exaggerate plasma TG levels [8][9][10]. Furthermore, exaggerated PPL is often present in patients with coronary heart disease (CHD) [11][12][13][14] and conditions associated with an increased risk of cardiovascular disease such as hypertension [15,16], obesity [15,17], diabetes mellitus [18,19], metabolic syndrome [20,21] and familial hypercholesterolaemia [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…The optimal treatment for weight loss in PCOS is unknown, with different macronutrient compositions promoted (17). In the general population, weight loss improves arterial compliance (18) and postprandial lipidemia (19,20), and increased protein meals (21) and reduced carbohydrate weight-loss diets (22) improve endothelial function and postprandial lipidemia. Although this provides preliminary evidence that modifying diet composition may improve postprandial lipidemia and vascular function, the effect of weight loss or diet composition on these factors in PCOS is currently unknown.…”
mentioning
confidence: 99%
“…A two-unit decrease in SAE was additionally reported as a significant predictor for cardiovascular events (odds ratio 1.50 95% confidence interval [CI] 1.19-1.88, P<.001) (15), suggesting our observed SAE improvement (1.5-units) is clinically relevant. Weight loss improves arterial compliance through modulating insulin resistance, inflammation, vasoactive substances, blood pressure (BP), or lipid metabolism, and improves postprandial lipidemia through improvements in insulin resistance stimulating lipoprotein lipase activity and triglyceride clearance (19,20). Although this suggests weight loss-related improvements in arterial compliance, and postprandial lipids are related to insulin resistance improvements, previous findings of reduced arterial compliance in insulin resistance-matched women with and without PCOS (4) suggests a deleterious effect of PCOS per se.…”
mentioning
confidence: 99%